PENGARUH PERILAKU ORANG TUA TERHADAP STATUS KEBERSIHAN GIGI ANAK DI SDN 03 KARANGJATI - Bambang Sutomo; Bedjo Santoso; Novi Atiyata Maula (Jurnal Kesehatan Gigi, 2017)
TITLETHE IMPACT OF PARENTS BEHAVIOR TO ORAL HYGIENE STATUS OF CHILDREN IN SDN 03 KARANGJATIABSTRACTHuman behavior is a result of all kinds of experiences as well as human interaction with the environment that materialized in the form of knowledge, attitudes and actions. The behavior of parents is very important to improve the oral hygiene of children and one of the efforts in the maintenance of oral health of children. The purpose of this study to determine the influence of parents' behavior toward the child dental hygiene level in SDN 03 Karangjati.This type of research is quantitative descriptive with method cross sectional. The population study was conducted on 03 fourth grade students Karangjati Semarang as many as 37 students. Sampling was done by total sampling. Gauges in this study were questionnaires, diagnostic sets, and sheet inspection. Data was analyzed by regression linear.The results showed that the level of hygiene of children's teeth are mostly in the moderate category and bad 26 people (70.3%), knowledge of parents in the poor category (54.1%), the attitude of the poor category (59.5%), actions of parents in either category (56.8%). test results obtained knowledge relationship with p.value = 0.001, attitude with p.value = 0.000, and act with p.value = 0.000, the test results influence the knowledge obtained by p.value = 0.748, attitude with p.value = 0.047, and act with p.value = 0.002. The conclusion is there is no relationship between knowledge, attitude and practice with the level of cleanliness of children's teeth. There is the influence of parental knowledge about dental hygiene of children. There is the influence attitudes and actions of parents on dental health children. Suggestions need for more participation for children to improve efforts to maintain dental hygiene and mouth that are in good condition. Keywords : Behavior of parents, a dental hygienist